2.7 μm emission properties of Er3+/Yb3+/Eu3+: SrGdGa3O7 and Er3+/Yb3+/Ho3+: SrGdGa3O7 crystals. (April 2016) - Xia, Houping; Feng, Jianghe; Ji, Yuexia; Sun, Yijian; Wang, Yan; Jia, Zhitai; Tu, Chaoyang
Abstract: Er 3+ /Yb 3+ /Eu 3+ : SrGdGa3 O7 and Er 3+ /Yb 3+ /Ho 3+ : SrGdGa3 O7 crystals were grown by Czochralski technology and detailed spectroscopic analyses were carried out. It was found that the spectra of Er 3+ /Yb 3+ /Eu 3+ : SrGdGa3 O7 crystal show weaker near-infrared emission and stronger mid-infrared emission as compared with Er 3+ /Yb 3+ : SrGdGa3 O7 crystal. Furthermore, the lifetime of the 4 I13/2 state decreases from 10.58 ms in Er 3+ /Yb 3+ : SrGdGa3 O7 crystal to 6.87 ms in Er 3+ /Yb 3+ /Eu 3+ : SrGdGa3 O7 crystal, that is, the self-saturation for 2.7 μm laser in Er 3+ /Yb 3+ /Eu 3+ : SrGdGa3 O7 crystal is suppressed greatly. These results indicate that the doping of Eu 3+ in Er 3+ /Yb 3+ : SrGdGa3 O7 crystal is beneficial to improve the 2.7 μm laser. In contrast, introducing Ho 3+ in Er 3+ /Yb 3+ : SrGdGa3 O7 crystal is adverse to realize Er 3+ -activated MIR laser operation. So Er 3+ /Yb 3+ /Eu 3+ : SrGdGa3 O7 crystal could be a potential MIR gain media for enhanced 2.7 μm laser. Highlights: MIR emission properties of Er 3+ /Yb 3+ /Re 3+ (Re 3+ =Ho 3+ and Eu 3+ ): SrGdGa3 O7 were studied. Er 3+ /Yb 3+ /Eu 3+ : SrGdGa3 O7 showed decreased NIR emission and enhanced MIR emission. The self-saturation problem in Er 3+ /Yb 3+ /Eu 3+ : SrGdGa3 O7 was suppressed greatly. Ho 3+ cannot act as depopulation ions to suppress the self-saturation effect.